Climbing performance in U23 and professional cyclists during a multi-stage race - Leo, P.; Spragg, J.; Simon, D.; Lawley, J.; Mujika, I. (International Journal of Sports Medicine, 2022)
The aim of this study was to analyze climbing performance across two editions of a professional multistage race, and assess the influence of climb category, prior workload, and intensity measures on climbing performance in U23 and professional cyclists. Nine U23 cyclists (age 20.8±0.9 years) and 8 professional cyclists (28.1±3.2 years) participated in this study. Data were divided into four types: overall race performance, climb category, climbing performance metrics (power output, ascent velocity, speed), and workload and intensity measures. Differences in performance metrics and workload and intensity measures between groups were investigated. Power output, ascent velocity, speed were higher in professionals than U23 cyclists for Cat 1 and Cat 2 (p=0.001-0.016). Workload and intensity measures (Worktotal, Worktotal·km-1, Elevationgain, eTRIMP and eTRIMP·km-1) were higher in U23 compared to professionals (p=0.002-0.014). Climbing performance metrics were significantly predicted by prior workload and intensity measures for Cat 1 and 2 (R2=0.27-0.89, p=0.001-0.030) but not Cat 3. These findings reveal that climbing performance in professional road cycling is influenced by climb categorization as well as prior workload and intensity measures. Combined, these findings suggest that Cat 1 and 2 climbing performance could be predicted from workload and intensity measures.